Recent advancements on the sustainable biochar based semiconducting materials for photocatalytic applications: A state of the art review. (1st January 2022) - Bhavani, Palagiri; Hussain, Murid; Park, Young-Kwon
Abstract: Renewable and sustainable energy production is essential for future technological requirements, owing to the ever-increasing environmental pollution caused by the use of non-renewable fossil fuels. The conversion of abundant solar energy to solar fuels by photocatalysis has been suggested as an adequate and alternative route to address the aforementioned issue. A wide range of catalysts have been studied, but their low photocatalytic efficiency due to rapid electron-hole recombination (e.g., C3 N4 ) and high cost (e.g., Pt) have limited their commercialization. There is an urgent need to develop economically/eco-friendly, highly efficient, and robust catalysts for enhanced photocatalysis to tackle the energy crisis and environmental issues. Semiconductor-based catalysts are commonly used as excellent compound materials for photocatalytic reaction applications because of their tunable energy band edge potential, abundance, and less poisonous characteristics. On the other hand, these have limitations due to charge recombination, poor stability, and low conductivity. The current review emphasizes the recent progress on semiconducting materials integrated with carbon (biochar) materials, which are a good choice to minimize these issues. This review summarizes the progress of recent research works for the development of highly active biochar-based composite systems to promote further developments of biochar-modified semiconductors in photocatalytic applications. Biochar has played a pivotal role in photocatalysis because of its fascinating benefits, such as a good support material, enhanced the specific surface area, and numerous surface active sites. These properties have led to high charge shuttling and acting as an electron reservoir, promoting greater charge separation and reducing the energy bandgap. The typical applications of biochar-modified photocatalytic materials are reviewed mainly in photocatalytic hydrogen production and other energy and environmental areas, such as carbon dioxide photo-reduction and the abatement of polluted water/air treatment under solar light irradiation. This review focuses on the recent trends and future prospects for the development of ecofriendly biochar-modified semiconductor photocatalysts. Graphical abstract: This review highlighted the synthesis of biochar and biochar modified catalysts, which includes various modification techniques for energy and environmental applications of photocatalytic water splitting, CO2 photoreduction and abatement of water/air pollutants. Image 1 Highlights: Different synthesis methods of biochar (BC) and BC based catalysts. Various activation and functionalization strategies of BC. Clarify the role of BC based catalysts in photocatalysis. Offer a new perspective to use BC based catalyst in energy and environmental fields.